1992
DOI: 10.1037/0735-7044.106.4.613
|View full text |Cite
|
Sign up to set email alerts
|

Visual and auditory spatial and nonspatial delayed-response performance by Korsakoff and non-Korsakoff alcoholic and aging individuals.

Abstract: Thirty-six male alcoholics (13 with Korsakoff's syndrome) and 24 controls performed visual and auditory delayed-response tasks sensitive to prefrontal cortical damage in nonhuman primates. Korsakoff patients were consistently impaired compared with other subjects. Impairments by Korsakoff patients were evident when demands were placed on visual processing time (brief stimulus durations), and the deficits became exaggerated with increased demands on short-term memory. Under the most difficult experimental condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 20 publications
3
33
0
Order By: Relevance
“…MRI (Di Sclafani et al, 1995;Pfefferbaum et al, 1995) and positron emission tomography (Adams et al, 1993;DaoCastellana et al, 1998;Martin et al, 1992) studies and neuropsychological testing (Oscar-Berman et al, 1992;Parsons, 1993;Parsons and Nixon, 1993) have implicated structural and functional involvement of the frontal lobes in uncomplicated alcoholics. That we observed reductions in cerebellar, but not frontal, [NAA] and [Cho] in our patients could reflect unrecognized localization of the VOI in an undamaged region of the frontal WM (Gonen et al, 2000).…”
Section: Discussionmentioning
confidence: 95%
“…MRI (Di Sclafani et al, 1995;Pfefferbaum et al, 1995) and positron emission tomography (Adams et al, 1993;DaoCastellana et al, 1998;Martin et al, 1992) studies and neuropsychological testing (Oscar-Berman et al, 1992;Parsons, 1993;Parsons and Nixon, 1993) have implicated structural and functional involvement of the frontal lobes in uncomplicated alcoholics. That we observed reductions in cerebellar, but not frontal, [NAA] and [Cho] in our patients could reflect unrecognized localization of the VOI in an undamaged region of the frontal WM (Gonen et al, 2000).…”
Section: Discussionmentioning
confidence: 95%
“…2) that persists chronically for many months after restitution of nutritional status . Comparative neuropsychological studies have shown that WKS affects delayed conditional discriminations of sensory stimuli in multiple sensory modalities, including delayed matching (DM) or nonmatching (DNM) tasks in which subjects choose between two response alternatives based on stimulus information presented in a preceding sample trial (Aggleton et al, 1988;Oscar-Berman et al, 1992;Squire et al, 1988). WKS patients also make more errors to criteria learning two choice discrimination and serial reversal learning tasks, although they retain the ability to perform discriminations at criteria once learned and exhibit positive transfer across a series of reversal problems (Oscar-Berman and Zola-Morgan, 1980).…”
Section: The Post Thiamine Deficiency (Ptd) Model Of the Wernicke-kormentioning
confidence: 99%
“…This type of working memory impairment has been seen in aged humans 35) and in WKS patients. 36) We have investigated the eŠects of cholinergic drugs on memory deˆcit in rats and mice after TD feeding. Memory deˆcit was improved by the administration of chronic physostigmine [intraperitoneally (i.p.…”
Section: Memory Deficit Induced By Thiamine Deficiencymentioning
confidence: 99%